Relación entre el gasto en educación pública y la productividad laboral en la región Loreto periodo 2010 – 2023 - Castellanos Salas, Ruth Neis (2025)
This research analyzes the relationship between public education spending and labor productivity in the Loreto region during the period 2010–2023. Using a quantitative approach and a non-experimental design, secondary data from official sources such as INEI, MEF, and MINEDU were collected and analyzed. Statistical techniques, including Spearman's correlation, were employed to determine the strength and direction of relationships between key variables: educational spending, formal employment rate, average income, and the educational attainment of the labor force. The results indicate a moderate positive relationship between education spending and labor productivity, as well as a significant correlation between per-student spending and the average level of education. However, it was found that the impact of education spending on formal employment and income depends on additional factors, such as education quality and labor market dynamics. This study concludes that while investment in education is crucial, it is insufficient to ensure substantial improvements in productivity and employment. The findings emphasize the need for comprehensive policies that optimize spending quality, promote formalization, and link education to strategic economic sectors for the sustainable development of Loreto.